Corpus iuris civilis. Edited by Paul Krueger. - Krueger, Paul, 1840-1926 (Cambridge Library Collection. Classics., 1877)
The most famous legal work of the ancient world was compiled at the order of the emperor Justinian (c.482-565) and issued in the period 529-34. It was intended to be a complete codification of all law, to be used as the only source of law in all the courts of the empire. The work was divided into three parts: the Codex Justinianus contained all of the extant imperial enactments from the time of Hadrian; the Digesta compiled the writings of great Roman jurists; and the Institutiones was intended as a textbook for law schools. However, Justinian later found himself obliged to create more laws, and these were published as the Novellae. This three-volume Latin edition of 1872-95, prepared by the great classical historian Theodor Mommsen (1817-1903) and his colleagues, is the culmination of centuries of palaeographical and legal studies. Volume 2 contains the Codex Justinianus.